1998
DOI: 10.3354/meps173067
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and bioturbation potential of macrofauna at four North Sea stations with contrasting food supply

Abstract: We investigated the macrobenth~c faunal composition, vertical distnbution, biomass, abundance and trophic structure in 4 North Sea sediments with contrasting quantity and quality of organic matter and with different hydrodynamic environments. The vertical distribution of macrofauna biomass generally followed the TOC (total organic carbon) profiles. The trophic structure reflected differences in relative quality of the organic matter In the high amount-high quality TOC sediment at the German Bight station, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
137
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(162 citation statements)
references
References 49 publications
18
137
0
7
Order By: Relevance
“…Thus, the functional biodiversity, reflected in different feeding modes and mobility, correlated with increased salinity. On 4 stations in the North Sea, with similar salinities, Dauwe et al (1998) found instead that the different composition of trophic groups of the benthic fauna was related to food availability, which also was suggested by Pearson and Rosenberg (1987).…”
Section: Functional Groupssupporting
confidence: 60%
See 1 more Smart Citation
“…Thus, the functional biodiversity, reflected in different feeding modes and mobility, correlated with increased salinity. On 4 stations in the North Sea, with similar salinities, Dauwe et al (1998) found instead that the different composition of trophic groups of the benthic fauna was related to food availability, which also was suggested by Pearson and Rosenberg (1987).…”
Section: Functional Groupssupporting
confidence: 60%
“…The brittle star Amphiura filiformis was one abundant species that was favoured by these changing conditions in food supply. In another study in the North Sea, Dauwe et al (1998) similarly found that the distribution of benthic communities was related to bottom dynamic factors and food supply. The highest diversity of trophic groups, largest individual sizes and the deepest distribution were found in sediment with organic matter of intermediate quality and quantity.…”
Section: Benthic-pelagic Couplingmentioning
confidence: 88%
“…Activity levels are very low (Fig. 14) across the Celtic Sea shelf compared to other UK shelf areas (Dauwe et al 1998;Teal et al 2008), and similar across all sediment types observed. The median ( f-SPI L med , typical shortterm depth of mixing), maximum ( f-SPI L max , maximum extent of mixing over the long-term) and mean ( f-SPI L mean , time dependent indication of mixing) mixed depths of particle redistribution are presented in Table 6.…”
Section: Macro-infauna ([1 Mm)mentioning
confidence: 52%
“…Species commonly found in the coastal habitat such as gobies, the pipefish Syngnathus rostellatus or the brittle star O. albida are known to have a high tolerance towards temperature and salinity variation (Ursin 1960;Knijn et al 1993). High nutrient input, together with a relatively long residence time of the water masses in the coastal habitat, could also result in intense algal blooms and, therefore, in increased food supply for benthic fauna (Dauwe et al 1998;Stöck and Kröncke 2001). Generally, most abiotic habitat characteristics changed gradually from the coast towards the Duck's Bill area (Table 4).…”
Section: Discussionmentioning
confidence: 99%